Ta có :
\(A=\frac{x^2+y^2+5}{x^2+y^2+3}=\frac{x^2+y^2+3+2}{x^2+y^2+3}=\frac{x^2+y^2+3}{x^2+y^2+3}+\frac{2}{x^2+y^2+3}=1+\frac{2}{x^2+y^2+3}\)
Để A đạt GTLN thì \(\frac{2}{x^2+y^2+3}\) phải đạt GTLN hay \(x^2+y^2+3>0\) và đạt GTNN
Do đó :
\(x^2+y^2+3=1\)
\(\Rightarrow\)\(x^2+y^2=-2\) ( loại vì \(x^2+y^2\ge0\) )
\(x^2+y^2+3=2\)
\(\Rightarrow\)\(x^2+y^2=-1\) ( loại )
\(x^2+y^2+3=3\)
\(\Rightarrow\)\(x^2+y^2=0\)
\(\Rightarrow\)\(\hept{\begin{cases}x^2=0\\y^2=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=0\\y=0\end{cases}}}\)
Suy ra :
\(A=\frac{x^2+y^2+5}{x^2+y^2+3}=\frac{0^2+0^2+5}{0^2+0^2+3}=\frac{0+0+5}{0+0+3}=\frac{5}{3}\)
Vậy \(A_{max}=\frac{5}{3}\) khi \(x=y=0\)
Chúc bạn học tốt ~